2020
DOI: 10.1111/jfs.12781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan edible coating enriched with lemon verbena extract and essential oil on the shelf life of vacuum rainbow trout (Oncorhynchus mykiss)

Abstract: In this research, the antioxidant and antibacterial characteristics of the chitosan (CH) coating incorporated with lemon verbena essential oil (LVEO) and extract (LVE) on the quality of the rainbow trout packed by vacuum packaging at 4°C were investigated. Samples evaluated include the following: Control, VP, CH, CH‐LVE 2%, CH‐LVEO 1%, and CH‐LVE 1%‐LVEO 0.5% for 16 days at 3 days intervals. All of the samples significantly reduced Psychrotrophic bacteria, total viable counts, Enterobacteriaceae, and H2S produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
29
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 34 publications
11
29
1
1
Order By: Relevance
“…Furthermore, the present study confirms the findings of Rezaeifar et al. (2020), who reported that the combined effect of the edible coating and citrus extracts reduced the growth of bacteria in fish fillets.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, the present study confirms the findings of Rezaeifar et al. (2020), who reported that the combined effect of the edible coating and citrus extracts reduced the growth of bacteria in fish fillets.…”
Section: Resultssupporting
confidence: 93%
“…The findings are in agreement with the study of Rezaeifar et al. (2020) where a chitosan coating enriched with lemon verbana extract retarded the growth of Enterobacteriaceae in rainbow trout fillets compared with control, and chitosan‐coated groups during refrigerated storage. Aerobic microorganism growth may be delayed when the fillets are wrapped by gelatin film.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Aloe vera gel [142,161,260,267,268] represents an important ingredient in chitosan-based formulations, since this extract has multiple benefits: anti-inflammatory, detoxifying, lowering cholesterol, improving metabolism, anti-ulceration, improving oral health, fighting cold and cough, etc. Therefore, besides edible coatings, aloe vera gel is both food and medicine, which is probably due to the content of glycosides aloin A and B (15-40%) [269].…”
mentioning
confidence: 99%
“…Pickering emulsions formed by chitosan-cellulose nanocrystals-oleic acid (10 or 20 g oleic acid/kg emulsion) were used for 'Bartlett' pears ripening prevention [270]. Chitosan-lemon verbena extract/essential oil for trout (Oncorhynchus mykiss) preservation [142].…”
mentioning
confidence: 99%